Automated tracking system assesments of player distances from the T at the moment the ball is hit for winners and losers of games in elite squash - Vuckovic, G.; Pers, J.; James, N.; Hughes, M. (World Congress of Performance Analysis of Sport VIII, 2008)
It appears from this analysis that at the elite level of squash the differences in movement patterns around the T between winners and losers of games are not significantly different. However the results show that winners tend to force their opponents to hit the ball when it is further away from the T, hence appearing to cause them to stretch slightly more, which may be a critical factor in explaining the small differences between winning and losing at this level. This suggests that measurable differences can be found that discriminate successful performance but this analysis has only had limited success. Why might this be the case? One factor that might have disguised true differences in performance may be the fact that game winners also tend to lose some rallies. Hence the data examined here contained a mixture of rallies where the winners won and lost the rallies. It may be more pertinent; therefore, to conduct future analyses at the rally level i.e. rally winners versus rally losers.